ADSP follow‐up study: NCRAD biospecimens. (December 2021) - Nudelman, Kelly N.H.; Faber, Kelley M.; Lacy, Kaci; Wilmes, Kristi; Marshall, Jeanine D.; Case, K. Rose; Mitchell, Colleen M.; Hobbick, Chris C.; Kunkle, Brian W.; Pericak‐Vance, Margaret A.; Cuccaro, Michael L.; Vance, Jeffery M.; et al.
Abstract: Background: The National Centralized Repository for Alzheimer's Disease and Related Dementias (NCRAD) is collaborating with the Alzheimer's Disease Sequencing Project (ADSP) to ensure that subjects with sequencing have available biospecimens. The latest phase of the ADSP, the Follow‐Up Study (ADSP‐FUS), is generating sequencing on additional subjects from diverse populations and ethnic groups; many of these subjects have samples available at NCRAD for validation and extension studies. Method: NCRAD collects, stores, and distributes biospecimens from subjects in studies included in the ADSP‐FUS, such as the National Institute on Aging Late Onset Alzheimer's Disease (NIA‐LOAD) Family Based Study, the Alzheimer's Disease Neuroimaging Initiative (ADNI), and subjects accrued by Alzheimer's Disease Research Centers (ADRCs). DNA for subjects in these studies is shipped to The American Genome Center (TAGC), under the direction of Dr. Clifton Dalgard, at the Uniformed Services University of the Health Sciences (USUHS), for whole genome sequencing. NCRAD has online catalogs for many of these cohorts, including information on biospecimens as well as demographic and clinical data, to help investigators identify and request biospecimens. Results: NCRAD has shipped >6, 000 DNA samples to USUHS for sequencing and inclusion in ADSP‐FUS from subjects with additional biospecimens housed at NCRAD. Many of these subjects have unique data sets or unique phenotypes, including the >1, 000 early onset Alzheimer's disease (AD) samples, 773 samples from ADNI, and >3, 000 AD cases/controls with clinical and/or autopsy data. The remainder were samples from cohorts focused on diverse populations and ethnic groups. For ADNI, genomic and cell line DNA, RNA, and lymphoblastoid cell lines (LCLs) are available to approved investigators; for NIA‐LOAD, genomic and cell line DNA and LCLs are available, with a subset also having peripheral blood mononuclear cells (PBMCs). For ADRC subjects, in addition to genomic or cell line DNA, RNA, plasma, serum, and PBMCs are available for select subjects. Currently, there are also iPSCs or fibroblasts available for 18 ADSP‐FUS subjects. NCRAD catalogs are currently available for the ADRCs and for NIA‐LOAD. Conclusion: NCRAD has extensive biospecimens available for investigators interested in validation or extension studies leveraging the whole genome sequencing data available through the ADSP‐FUS.